Analisis Peranan Pengendalian Internal Atas Penjualan, Piutang Dan Penerimaan Kas Pada PT. Alfa Scorpii - Lili Fizriah, Henny Andriyani Wirananda (Journal Economy and Currency Study (JECS), 2022)
This study aims to determine the role of internal control over sales, accounts receivable and cash receipts at PT. Alfa Scorpii. The data used in this study is primary data, the subject in this study is PT. Alfa Scorpii. While the object in this research is internal control. Data collection techniques were carried out by observation, interviews and documentation studies. The data analysis technique used is to review the role of internal control over sales, accounts receivable and cash receipts at PT. Alfa Scorpii, by collecting data and then studying and reviewing data based on interviews and documentation, in order to obtain results from the role of internal control over sales, receivables and cash receipts at PT. Alfa Scorpii. From the overall research results indicate that the role of internal control over sales at PT. Alfa Scorpii has been running well because there is a separation of duties and authority between employees so as to minimize errors and fraud that might occur in the company. The role of internal control over receivables at PT. Alfa Scorpii has separated the parts according to their respective fields, so there is no confusion when carrying out the tasks assigned by superiors and the company becomes safe because it can reduce fraud that can be caused by these employees. Internal control over cash receipts at PT Alfa Scorpii has not been carried out according to procedures because employees at the inputting cash receipts section sometimes often cover deposits from other people due to delaying the recording of cash so as to steal money. The advice given from the research results is internal control at PT. Alfa Scorpii has done quite well in the company but there is still control in the cash receipts section that is still not done well, it is better to warn employees so that it is carried out properly.